基于Sketch的跨平台界面开发方法和系统、计算机设备和介质 (2025)
本发明实施例公开一种基于Sketch的跨平台界面开发方法和系统、计算机设备和介质。在一具体实施方式中，该方法包括：接收服务器发送的代码化界面设计组件，代码化界面设计组件包括基于界面设计原图的跨平台描述文件和Web文件；基于代码化界面设计组件利用Sketch插件生成界面布局文件，界面布局文件包括至少一个图案面板、以及与每个图案面板对应的数据和图片；将界面布局文件上传至服务器，以使得服务器将界面布局文件传输至第三开发端以形成跨平台界面。该实施方式通过利用Sketch插件将自服务器接收的代码化界面设计组件生成界面布局文件，使第三开发端生成跨平台界面，实现了重复的无差异性的界面开发。 The embodiment of the invention discloses a cross-platform interface development method and system based on Sketch, computer equipment and a medium. In a specific implementation mode, the method comprises the steps: receiving a code interface design assembly sent by a server, wherein the code interface design assembly comprises a cross-platform description file and a Web file based on an interface design original drawing; generating an interface layout file by utilizing a Sketch plug-in based on the code interface design component, wherein the interface layout file comprises at least one pattern panel and data and pictures corresponding to each pattern panel; uploading the interface layout file to a server, so that the ser